Practical works on astronomy classes (Pedagogy of Higher and Secondary Education, 2012)
Malchenko S. L. Practical works on astronomy classes.Students and pupils are able to see the astronomical phenomenon of new parties if they using on the lessons received knowledge to solve practical tasks, which was obtained by observing. In this paper proposed practical work without special equipment and is presented a practical session on «A distances to a stars». Also were shown that the performance of such work, problem solving on the lessons astronomy at school and in higher education are essential for the development of self-thinking creative person that can make your own conclusions.
Keywords: practical work; astronomy; distance to a stars; stellar constellation